مساهمة ادارة المعرفة في تحسين ادارة القيمة بالمنظمات دراسة ميدانية بمؤسسة روائح الورود بالوادي - بثينة, مناصر; يمينة, لعقاب (University of eloued جامعة الوادي, 2020)
"هدفت هذه الدراسة إلى التعرف على مدى مساهمة إدارة المعرفة في تطوير إدارة القيمة في مؤسسة روائح الورود، وقد اكتسبت الدراسة أهمية بالغة من خلال اهتمام المتزايد من طرف المنظمات الأعمال لهذا الموضوع على اختلاف أنواعها وأحجامها. حيث استخدمنا المنهج الوصفي التحليلي لملائمته لأعراض الدراسة، حيث كانت الاستبانة هي الأداة الرئيسية لجمع البيانات، وكان حجم العينة 100 استبانة واستردد منها 76 استبانة أي بنسبة 76 %، ولتحليل البيانات واختبار الفرضيات تم استخراج برنامج إحصائي spss v25 . أهم النتائج المتوصل إليها من هذه الدراسة: - وجود علاقة طردية بين المتغير المستقل المعرفة والمتغير التابع إدارة القيمة. - وجود علاقة معنوية متوسطة بين أبعاد إدارة المعرفة (توليد، نشر، تطبيق) وإدارة القيمة. - لا توجد فروق ذات دلالة إحصائية عند مستوى دلالة (0.05 ≥ α) في آراء المستجوبين حول تطبيق إدارة المعرفة لإسهام في تحسين إدارة القيمة تعزى لخصائص الديموغرافية (الجنس، العمر، المستوى العلمي، سنوات الخبرة والمستوى الوظيفي) لدى عينة الدراسة؟ ""This study aimed to identify the extent of the contribution of knowledge management to the development of value management in the rose scents enterprise, and the study has gained great importance through the increasing interest of business organizations in this matter of all kinds and sizes. Where we used the descriptive and analytical method for its suitability to the symptoms of the study, as the questionnaire was the main tool for data collection, and the sample size was 100 questionnaires, of which 76 questionnaires were retrieved, i.e. 76%, and for data analysis and hypothesis testing, a statistical program spss v25 was extracted knowledge management The most important findings from this study: - The existence of a direct relationship between the independent variable known and the dependent variable value management - There is a moderate moral relationship between the dimensions of knowledge management (generation, dissemination, application) and value management - Is present at a significance level of 0.05 ≥ α in the knowledge management position to contribute to improving the management of the value attributable to the demographic characteristics (gender, level, scientific level, experience and job level) of the study sample? "
مذكرة ماستر ادارة اعمال
Keywords: إدارة المعرفة، توليد المعرفة، نشر المعرفة، تطبيق المعرفة، إدارة القيمة.; knowledge management, Knowledge generation, Spreading knowledge, Knowledge application, Value management.